Um Rei orientado pela lei: (Dt 17,14-20) - Silva, João Claudio Rufino Rodrigues (2014)
This dissertation aims to present an exegetical study of a legislative text on Pentateuch: Dt 17,14-20, the law of the king . It follows the style of commentary. The research advances with the biblical tradition in question. In each one of the three chapters there are two kinds of investigations: first, a linguistic and literary study which includes translation, morphological analysis; second, a theological and historical commentary which utilizes researches about de cultural ambient, theological and literary motifs present in the Pentateuch and in the deuteronomistic work. In all this paper is shown the the Ancient Near East influence in the law of the king and in what it is different from its context. Israel has the permission to establish one king over himself. But to do it they need to follow some prescriptions. Either the king must to do it for there three prohibitions to him. He cannot multiply horses, women and healthy. Even more, he must to copy the law, read it practice it every day. And doing this his heart will not lift up upon his brothers